2021
DOI: 10.1080/21655979.2021.1973863
|View full text |Cite
|
Sign up to set email alerts
|

Whole-transcriptome analysis of rat cavernosum and identification of circRNA-miRNA-mRNA networks to investigate nerve injury erectile dysfunction pathogenesis

Abstract: There is growing evidence that circular RNAs (circRNAs) play a vital role in many kinds of diseases, including erectile dysfunction (ED). Nevertheless, the role of circRNAs in cavernous nerve-damaging ED (CNI-ED) is unknown. Here, we aimed to discover novel circRNAs, probed their potential role in the CNI-ED, and construct a ceRNA network of circRNAs. Twelve male Sprague Dawley rats were randomly divided into 2 groups by us: bilateral cavernous nerve crush (BCNC) and control groups. Four weeks after surgery, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In addition, similar time-dependent fluctuations in circulating miRNA-21 expression have also been observed in patients with post-myocardial infarction ( 27 ). Further studies are needed to reveal any potential link between miRNAs and circRNAs or miRNAs ( 28 ) correlated with prognosis and predictive value for heart failure ( 11 ) in CVD patients across different comorbidities ( 29 , 30 ) and populations, as well as therapeutic agents in treatment ( 31 , 32 ), including in female CVD patients. Studies have also investigated the potential use of circulating serum miRNA and fecal miRNA expression as non-invasive markers for early detection ( 33 ), which might aid in guiding therapeutics ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar time-dependent fluctuations in circulating miRNA-21 expression have also been observed in patients with post-myocardial infarction ( 27 ). Further studies are needed to reveal any potential link between miRNAs and circRNAs or miRNAs ( 28 ) correlated with prognosis and predictive value for heart failure ( 11 ) in CVD patients across different comorbidities ( 29 , 30 ) and populations, as well as therapeutic agents in treatment ( 31 , 32 ), including in female CVD patients. Studies have also investigated the potential use of circulating serum miRNA and fecal miRNA expression as non-invasive markers for early detection ( 33 ), which might aid in guiding therapeutics ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…We identified lncRNA as previously described 14 using coding potential analysis with CNCI, CPC, and PFAM. Differentially expressed lncRNAs (DE lncRNAs) were defined with DESeq2 (adjust P value < 0.05, |FC| > 1.3).…”
Section: Methodsmentioning
confidence: 99%
“…Protein coding RNAs (mRNAs) and noncoding RNAs interact and influence each other, playing an important role in gene expression and regulation. Numerous studies have shown that long noncoding RNAs (lncRNAs), which are typically longer than 200 nucleotides, 11 and microRNAs (miRNAs), which are small noncoding single-stranded RNA molecules, [12][13][14][15] mutually controlled each other's expression levels and collaborated to modulate mRNA expression. 16,17 Several lncRNAs and miRNA have been linked to lipopolysaccharide (LPS)-induced cardiac dysfunction in the mouse heart 18,19 and play an important role in myocardial protection.…”
Section: Introductionmentioning
confidence: 99%